IMPACTS OF GAME SPECIFIC EXERCISE ON SKILL PERFORMANCE VARIABLES AMONG HANDBALL PLAYERS - S. Palani; Dr. P. Sridar (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The point of the present study was to find out the impacts of game specific exercise on skill performance variables among handball players. To achieve the purpose of the study male handball players were selected from Government Arts and Science College, (Affiliated to Bharathiar University, Coimbatore) Modakkurichi, Erode, Tamilnadu, India. The subject’s age ranges from 19 to 24 years. The selected subjects were divided into two equal groups consists of 15 male handball players each namely experimental group and control group. The experimental group underwent a game specific exercise package programme for twelve weeks. The control group was not taking part in any training during the course of the study. Dribbling and shooting was taken as criterion variable in this study. The selected subjects were tested on dribbling and shooting was measured through coaches rating. Pre-test was taken before the training period and post- test was measured immediately after the twelve-week training period. Statistical technique‘t’ ratio was used to analyze the means of the pre-test and post test data of experimental group and control group. The results revealed that there was a significant difference found on the criterion variable. The difference is found due to game specific exercise package given to the experimental group on dribbling and shooting when compared to control group.